# solvingTransformations.frink

``` // These transformations try to solve simple equations and teach Frink to // solve basic algebraic equations for the specified variable. // //  For example, enter: //    solve[3(x+y) === 10, x] // // (Right now this requires the double-equals sign because Frink currently //  requires that the left-hand-side of an assignment operator //  ( = ) can actually be meaningfully assigned to, which may be // a constraint that needs to get loosened for temporary values. // This creates a named list of transformations called "solving" that we // can apply by name later. transformations solving {    // Change sqrt[x] into a power.    sqrt[_x] <-> _x^(1/2)    // Move the variable we're solving for to the left side of the equation    // if it's only on the right side of the equation.    solve[_left === _right, _x] :: (freeOf[_left, _x] AND expressionContains[_right, _x])  <-> solve[_right === _left, _x]    // Bailout condition    solve[_x === _z, _x] :: freeOf[_z, _x]  <-> _x === _z    // Quadratic equations     solve[(_a:1) _x^2 + (_b:1) _x === _c, _x] :: freeOf[_c, _x] <-> [ solve[_x === (-_b + (_b^2 - 4 _a (-_c))^(1/2)) / (2 _a), _x], solve[_x === (-_b - (_b^2 - 4 _a (-_c))^(1/2)) / (2 _a), _x] ]    // If both sides have an x, divide out x terms from right. //   solve[_a === (_c:1) _x^(_b:1), _x] :: expressionContains[_a, _x] <-> solve[_a / _x^_b === _c, _x]    // First move additive terms    // Move all x-containing terms to left    solve[_a === _c, _x] :: (expressionContains[_a, _x] && expressionContains[_c, _x]) <-> solve[_a - _c === 0, _x]    // Move all non-x-containing terms to right.     solve[_a + _b === _c, _x] :: (freeOf[_a,_x] AND expressionContains[_b, _x]) <-> solve[_b === _c - _a, _x]    // Then move multiplicative terms.    solve[_a * _b === _c, _x] :: (freeOf[_a,_x] AND expressionContains[_b, _x]) <-> solve[_b === _c / _a, _x]    // Flip inverse exponents.    solve[_a^_k is isNegative === _b, _c] :: expressionContains[_a, _c] <-> solve[_a^-_k === _b^-1, _c]    // Solve for two terms containing c    solve[_a _c + (_b:1) _c === _d, _c] :: freeOf[_a, _c] && freeOf[_b, _c] && freeOf[_d,_c] <->  solve[_c === _d / (_a + _b), _c]    // Solve for negative and positive exponents on same side.    solve[(_c1:1) _a^_k is isNegative + (_c2:1) _a^(_j:1) === _b, _c] :: expressionContains[_a, _c] && freeOf[_c1, _c] && freeOf[_c2, _c] <-> solve[_c1 + _c2 _a^(_j-_k) === _b _a^-_k, _c]    // Very general negative and positive exponents on same side.    solve[(_a:1) _x^_b is isNegative + _c === _d, _x] :: expressionContains[_c, _x] <-> solve[_a + _c _x^-_b === _d _x^-_b, _x]    // Help the solver to factor an expression.    solve[(_a:1) _x^_b + _c _x^_b === _d, _x] <-> solve[_x^_b === _d / (_a + _c), _x]    // x in numerator and denominator (denominator has additive term.)    solve[(_b:1) _x / ((_a:1) _x + _y) === _z, _x] :: freeOf[_b, _x] && freeOf[_a, _x] && freeOf[_y, _x]  <-> solve[_x === _z (_a _x + _y) / _b, _x]    // x in denominator of complicated fraction and outside fraction.    solve[(_a:1) _x + (_b:1) / _d === _e, _x] :: expressionContains[_d, _x] <-> solve[_a _x _d + _b === _e _d, _x]    // Solve for squared terms.    // Results are a list of two different solutions.    solve[_a^_k is isPositive === _b, _c] :: expressionContains[_a, _c] AND (_k mod 2 == 0) <-> [ solve[_a^(_k/2) === _b^(1/2),_c] , solve[_a^(_k/2) === -_b^(1/2), _c ] ]    // a x +  b (d+ (c x)^(1/2)) === z //   solve[(_a:1) _x + (_b:1) ((_d:0) + ((_c:1) _x)^(1/2)) === _z, _x] :: freeOf[_a, _x] and freeOf[_b,_x] and freeOf[_c, _x] and freeOf[_d, _x] and freeOf[_z, _x] <-> [ solve[sqrt[-4 _a _b^3 _c _d + 4 _a _b^2 _c _z + _b^4 _c^2] - 2 _a _b _d + 2 _a _z + _b^2 _c, _x], solve[-sqrt[-4 _a _b^3 _c _d + 4 _a _b^2 _c _z + _b^4 _c^2] - 2 _a _b _d + 2 _a _z + _b^2 _c, _x] ]    // Force grouping of terms together.  Note that this is the inverse of the    // distributive transform below and could cause loops.    solve[(_a:1) _x + (_b:1) _x + (_c:0), _x] <-> solve[_x (_a + _b) + _c, _x]        // a x^(1/2) + b x== d    //   solve[((_a:1) _x^(1/2)) + (_b:1) _x  === _d, _x] :: freeOf[_a, _x] and freeOf[_b,_x] and freeOf[_d, _x] <-> [ solve[_x === (_a sqrt[_a^2 + 4 _b _d] + _a^2 + 2 _b _d)/(2 _b^2), _x], solve[_x === (-_a sqrt[_a^2 + 4 _b _d] + _a^2 + 2 _b _d)/(2 _b^2), _x]]    // General solving help when a term includes x + x^(1/2) terms.    // Shift the x^(1/2) term to one side of the equals sign and square both    // sides.  This generally lets it be solved by the quadratic equation.    solve[_a + (_d:1) _b^(1/2) === _c, _x] :: expressionContains[_a, _x] and expressionContains[_b, _x] and freeOf[_c, _x] and freeOf[_d, _x]   <-> solve[(_a - _c)^2 === _d^2 _b, _x]    // General solving help when a term includes x *  x^(1/2) terms.    // Shift the x^(1/2) term to one side of the equals sign and square both    // sides.    solve[_a _b^(1/2) + (_d:0) === _c, _x] :: expressionContains[_a, _x] and expressionContains[_b, _x] and freeOf[_c, _x]   <-> solve[_b _a^2 === (_c-_d)^2, _x]    // General solving help when a term includes x *  x^(-1/2) terms.    // Shift the x^(-1/2) term to one side of the equals sign and square both    // sides.    solve[_a _b^(-1/2) + (_d:0) === _c, _x] :: expressionContains[_a, _x] and expressionContains[_b, _x] and freeOf[_c, _x]   <-> solve[_b === a^2 / (_c-_d)^2, _x]    // General solving help when a term contains a x + b (c + d x)^2 terms.    // Expand out (c + d x) which usually allows the equation to be solved    // with the quadratic equation.    // TODO:  Generalize this for cubed terms, etc    solve[(_a:1) + (_b:1) (_c + (_d:1) _x)^2 === _f, _x] :: expressionContains[_a, _x] and freeOf[_c, _x] and freeOf[_f, _x] <-> solve[_a + _b (_c^2 + 2 (_c _d _x) + _d^2 _x^2) === _f, _x]        // a x (b + c x^2)^(-1/2) == d //   solve[(_a:1) _x (_b + (_c:1) _x^2)^(-1/2) === _d, _x]  <-> [solve[_x === i _b^(1/2) _d / (_c _d^2 - _a^2)^(1/2), _x], solve[_x === -i _b^(1/2) _d / (_c _d^2 - _a^2)^(1/2), _x]]    // _a + (_b + _x)^2 == d  with a containing x.  Multiply out the parens.    solve[_a + (_b + (_c:1) _x)^2 === _d, _x] :: expressionContains[_a, _x] <-> solve[_a + _b^2 + 2 _b _c _x + _c^2 _x^2 === _d, _x]    // Factor out 3 terms.  TODO:  Generalize this!    solve[(_a:1) _x + _b _x + _c _x === _d, _x] <-> solve[(_a + _b + _c) _x === _d, _x]        // Solve for powers of 3, 6, 9, etc.    solve[_a^_k is isPositive === _b, _c] :: expressionContains[_a, _c] AND (_k mod 3 == 0) <-> [ solve[_a^(_k/3) === _b^(1/3),_c] , solve[_a^(_k/3) === -((-1)^(1./3)) _b^(1/3), _c ], solve[_a^(_k/3) === ((-1)^(2./3)) _b^(1/3), _c ] ]        // Solve for rational exponents    solve[_a^_k is isRational === _b, _c] :: expressionContains[_a, _c] <->  solve[_a === _b^(1/_k),_c]        // Gah!  Cubic equations!    // See http://en.wikipedia.org/wiki/Cubic_function#General_formula_of_roots    // TODO:  Find a way to store repeated temporary parts of results into variables.    // TODO:  Handle cases where b or c or both are 0!    solve[(_a:1) _x^3 + (_b:1) _x^2 + (_c:1) _x === _d, _x] :: freeOf[_d, _x] <-> [x === -_b/(3 _a) - (2^(1/3) (-729 _a^4 _b^2 + 2187 _a^5 _c))/(2187 _a^3 (-2 _a^6 _b^3 + 9 _a^7 _b _c - 27 _a^8 _d + 3 sqrt sqrt[-(_a^14 _b^2 _c^2) + 4 _a^15 _c^3 + 4 _a^14 _b^3 _d - 18 _a^15 _b _c _d + 27 _a^16 _d^2])^(1/3)) + (-2 _a^6 _b^3 + 9 _a^7 _b _c - 27 _a^8 _d + 3 sqrt sqrt[-(_a^14 _b^2 _c^2) + 4 _a^15 _c^3 + 4 _a^14 _b^3 _d - 18 _a^15 _b _c _d + 27 _a^16 _d^2])^(1/3)/(3 2^(1/3) _a^3) && _a != 0,     (x === -_b/(3 _a) + ((1 + i sqrt) (-729 _a^4 _b^2 + 2187 _a^5 _c))/(2187 2^(2/3) _a^3 (-2 _a^6 _b^3 + 9 _a^7 _b _c - 27 _a^8 _d + 3 sqrt sqrt[-(_a^14 _b^2 _c^2) + 4 _a^15 _c^3 + 4 _a^14 _b^3 _d - 18 _a^15 _b _c _d + 27 _a^16 _d^2])^(1/3)) - ((1 - i sqrt) (-2 _a^6 _b^3 + 9 _a^7 _b _c - 27 _a^8 _d + 3 sqrt sqrt[-(_a^14 _b^2 _c^2) + 4 _a^15 _c^3 + 4 _a^14 _b^3 _d - 18 _a^15 _b _c _d + 27 _a^16 _d^2])^(1/3))/(6 2^(1/3) _a^3) && _a != 0),    (x === -_b/(3 _a) + ((1 - i sqrt) (-729 _a^4 _b^2 + 2187 _a^5 _c))/(2187 2^(2/3) _a^3 (-2 _a^6 _b^3 + 9 _a^7 _b _c - 27 _a^8 _d + 3 sqrt sqrt[-(_a^14 _b^2 _c^2) + 4 _a^15 _c^3 + 4 _a^14 _b^3 _d - 18 _a^15 _b _c _d + 27 _a^16 _d^2])^(1/3)) - ((1 + i sqrt) (-2 _a^6 _b^3 + 9 _a^7 _b _c - 27 _a^8 _d + 3 sqrt sqrt[-(_a^14 _b^2 _c^2) + 4 _a^15 _c^3 + 4 _a^14 _b^3 _d - 18 _a^15 _b _c _d + 27 _a^16 _d^2])^(1/3))/(6 2^(1/3) _a^3) && _a != 0),    (x === (-_c - sqrt[_c^2 - 4 _b _d])/(2 _b) && _a === 0 && _b != 0),    (x === (-_c + sqrt[_c^2 - 4 _b _d])/(2 _b) && _a === 0 && _b != 0),    (x === -(_d/_c) && _b === 0 && _a === 0 && _c != 0)]        // Replace floating-point approximation to zero with integer 0.    0. <-> 0        // Some simplifying rules that actually aren't appropriate if you're    // tracking units.  These are not really valid because 0 feet != 0 days    // and 0 feet + 0 is not units-correct.    // TODO:  FIX THIS!   We need a pattern that matches units with magnitude    // of zero.    0 _x <-> 0 //   0 + _x <-> _x    1 _x <-> _x    ln[e] <-> 1    ln <-> 0    log <-> 1    log <-> 0    log[_a, _b] <-> ln[_a] / ln[_b]    // This transforms rules in terms of log base 10 into equations of    // natural log.  This makes a lot of different types of equations more    // readily solved by already-existing rules:  for example, LambertW rules,    // (see powerTransformations.frink)    // and eliminates the need to rewrite all of these rules in multiple forms.    log[_a] <-> ln[_a] / ln    // Simplifying rule    e^ln[_x] <-> _x        // Simplifying rule    e^(_a ln[_b]) <-> _b^_a    // Simplifying rule    ln[_a ^ _b] <-> _b ln[_a]    // Simplifying rule    log[_a ^ _b] <-> _b log[_a]    // Exponentiate out parts.    (_a _b)^_c <-> _a^_c _b^_c         // Distribute (to often clarify and simplify)    // (Note: this is often disadvantageous when using    // interval arguments as intervals are subdistributive and the result    // may be wider.)    _a (_c + _d) <-> _a _c + _a _d    // Combine coefficients of x;    // This may cause loops with the above expression. //   _a _x + _b _x + (_c:0) <-> (_a + _b) _x + _c //   (_a + _b)^_k :: isInteger[_k] AND _k >= 2  <->  (_a^2 + 2 _a _b + _b^2)(_a + _b)^(_k-2) } "solvingTransformations.frink included ok!" ```

This is a program written in the programming language Frink.
For more information, view the Frink Documentation or see More Sample Frink Programs.

Alan Eliasen was born 18353 days, 13 hours, 7 minutes ago.